Indirect Restorations and Fixed Prosthodontics: Materials and Techniques Used by General Dentists of New Zealand. (10th January 2019) - Brunton, Paul A.; Ratnayake, Jithendra; Loch, Carolina; Veerasamy, Arthi; Cathro, Peter; Lee, Robert
Abstract : Background . To investigate the selection and use of materials and techniques for core buildup, indirect restorations, and fixed prosthodontics by general dentists in New Zealand. Methods . A questionnaire comprising 19 sections and 125 questions was distributed via mail to 351 general dentists in New Zealand who were selected from the Dental Council of New Zealand's 2016 register. Results . The majority of the respondents (68.8%) reported using resin composite light-cured materials for the core buildup of vital posterior teeth. A large number of respondents (52%) did not use dentine pins, with the majority of them (25%) being recent graduates (<10 years). Fibre posts were used by 61.6% of the dentists surveyed. The majority of dentists (54.6%) reported using addition-cured silicone impression material for crown and bridge impressions. Glass-ionomer cements (37.5% of participants) and resin-modified glass-ionomer cements (35.8%) were the most common luting cements used. Direct resin composite veneers were the preferred material of choice rather than indirect restoration of anterior teeth (40.4%). Conclusions . The study showed that New Zealand dentists surveyed are using current state-of-the-art materials and techniques, with their choice of material being greatly influenced by clinical indications and patients aesthetic demands.